2011
DOI: 10.1063/1.3610998
|View full text |Cite
|
Sign up to set email alerts
|

Improved initial drop in operational lifetime of blue phosphorescent organic light emitting device fabricated under ultra high vacuum condition

Abstract: A blue phosphorescent organic light emitting device fabricated under the ultra high vacuum (UHV) condition of 6.5 × 10−7 Pa decreases the initial luminance drop upon lifetesting under a constant dc current of 15 mA/cm2 by 3 times compared to a device fabricated under a high vacuum (HV) condition of 7.6 × 10−6 Pa resulting in a 23% increase in half lifetime. We calculate a water content of 10−4 mol. % in the UHV device emissive layer (EML) and 10−2 mol. % in the HV device EML. We discuss the effects of water on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…Yamamoto et al 26 reported that water contamination of organic films during deposition leads to an accelerated initial degradation when the deposition background pressure is 45 Â 10 À 8 Torr for PHOLEDs, almost identical to that of D1. In our case, organic films were deposited in a system with a base pressure of 5 Â 10 À 7 Torr; however, the TPA model ignores extrinsic effects such as water contamination.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Yamamoto et al 26 reported that water contamination of organic films during deposition leads to an accelerated initial degradation when the deposition background pressure is 45 Â 10 À 8 Torr for PHOLEDs, almost identical to that of D1. In our case, organic films were deposited in a system with a base pressure of 5 Â 10 À 7 Torr; however, the TPA model ignores extrinsic effects such as water contamination.…”
Section: Resultsmentioning
confidence: 96%
“…To account for the effect of water contamination during device fabrication 26 , L(0) is normalized to 0.95 and DV(0) ¼ 0.2 V (at 3,000 cd m À 2 ) and 0.3 V (at 1,000 cd m À 2 ) for D1-D3, and 0.1 V (at 3,000 cd m À 2 ) and 0.15 V (at 1,000 cd m À 2 ) for D1S and D3S. The data are fit to the TPA model using the exciton density profiles in Fig.…”
Section: Nðxþdxmentioning
confidence: 99%
“…In addition, this figure covers a wide variety of building blocks, including arene, carbazole, triphenylamine, fluorene, benzothiophene and even polar moieties such as benzophenone, pyridine and triazine, making this approach broadly applicable. We also note that our approach enables subsequent solution processing onto the EML without having to use water, which is detrimental to device efficiency and stability [27][28][29][30] .…”
Section: Solvent Resistance Testmentioning
confidence: 99%
“…Lifetime is also an important device characteristic of the blue PHOLEDs and the lifetime level of the blue PHOLEDs is still far below that of the blue fluorescent OLEDs [7][8][9]. There have been several papers reporting the lifetime of the blue PHOLEDs and the improvement of the device lifetime was mostly made by engineering the device architecture [7,8].…”
mentioning
confidence: 97%
“…There have been several papers reporting the lifetime of the blue PHOLEDs and the improvement of the device lifetime was mostly made by engineering the device architecture [7,8]. Common materials were used in the device structure and no high triplet energy hole transport material was used in the device structure because no stable high triplet energy hole transport material is available.…”
mentioning
confidence: 99%